Determinan Permintaan Mobil Low Cost Green Car (LCGC) di Kota Pekanbaru: Studi Kasus Daihatsu Ayla - M. Rafi Atthariq; Mardiana, Indri Yovita (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the determinants of demand for Low Cost Green Car (LCGC) Daihatsu Ayla in Pekanbaru City. Using secondary data from 2014-2024 obtained from BPS, PT Astra Daihatsu Motor Pekanbaru, and GAIKINDO, this research employs multiple linear regression analysis. The results indicate that the price of Daihatsu Ayla has a significant positive effect on demand, the competitor's price (Toyota Agya) has no significant effect, while consumer income has a significant negative effect on demand. The coefficient of determination (R²) of 0.897 indicates that 89.7% of demand variation can be explained by these three variables. These findings suggest that Ayla functions as an inferior good in Pekanbaru's market, where consumers tend to upgrade to higher segments when their income increases